ENT 530 Social Media Portfolio / Fatin Syafiqah Mohd Zaidi - Mohd Zaidi, Fatin Syafiqah (2019)
The business name is Fancy Handsock FS which are selling the handsock to a women out there. The purpose of this business is to encourage a women to cover their aurah in a beautiful ways. Therefore, the target customer is for students because I am selling this at UiTM Puncak Alam so that they are the main target customer but people that stay outside of UiTM Puncak Alam also can buy the handsock too. Apart from that, the price that I put is very reasonable to the students besides the quality cloth is very comfort to them to wear.